1989
DOI: 10.1073/pnas.86.24.9697
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 8-hydroxy-2'-deoxyguanosine as a biological marker of in vivo oxidative DNA damage.

Abstract: DNA is subject to constant oxidative damage from endogenous oxidants. The oxidized DNA is continuously repaired and the oxidized bases are excreted in the urine. A simple routine analytical procedure is described for urinary 8-hydroxy-2'-deoxyguanosine, an oxidative DNA damage adduct, as an indicator of oxidative damage in humans and rodents. This adduct was purified from human urine and characterized. The described assay employs a series of solidphase extraction steps that separate 8-hydroxy-2'-deoxyguanosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
388
0
6

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 670 publications
(406 citation statements)
references
References 22 publications
12
388
0
6
Order By: Relevance
“…Yoshida et al [42] found a good correlation (r ¼ 0.88) between urinary 8-OHdG levels obtained with using ELISA (same kit as in our study) and HPLC-ECD. Urinary 8-OHdG excretion is not affected by the dietary intake of 8-OHdG [43].…”
Section: Discussionmentioning
confidence: 93%
“…Yoshida et al [42] found a good correlation (r ¼ 0.88) between urinary 8-OHdG levels obtained with using ELISA (same kit as in our study) and HPLC-ECD. Urinary 8-OHdG excretion is not affected by the dietary intake of 8-OHdG [43].…”
Section: Discussionmentioning
confidence: 93%
“…The most prevalent mutation type was the G:C→T:A transversion ( Fig. 2A), possibly reflecting the mutagenicity of guanine oxidative products produced in culture under ambient oxygen concentrations (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…When damaged DNA is repaired, 8-OHdG produced is excreted in urine without further metabolism [9,10]. Urinary 8-OHdG has been widely used as a sensitive marker of oxidative DNA damage and of the total systemic oxidative stress in vivo [11,12]. Recent reports [13][14][15] found an increased 8-OHdG level in mononuclear cells and urine in patients with insulin-dependent diabetes mellitus (IDDM) and non-insulin-dependent diabetes mellitus (NIDDM).…”
Section: Introductionmentioning
confidence: 99%